DAYA SAING INDUSTRI INDONESIA DALAM MASYARAKAT EKONOMI ASEAN :MEA - Zulkarnain Zulkarnain (Universitas Nasional, 2015)
Liberalization of trade brings with it consequences in competition and ganing market potentials. MEA or Asean Economic Community as liberalization call for preparedness of Indonesia to compete. With the population of about 250 million people the country would be tehe target market of products coming across the Asean countries and beyond. When the industry of the country is prepared in MEA market covering 617.68 million people MEA would be the blessing for Indonesia and more people in the country would gain more benefits.